Criminal Liability for Large-scale Social Distancing Violations - Apriliya Nursyabani Bachtyar; Mochammad Tanzil Multazam (Universitas Muhammadiyah Sidoarjo, 2021)
The legal politics of establishing large-scale social restriction regulations in the context of accelerating the handling of the Corona Virus Disease 2019 (COVID-19) which was formed in 2020. In this case, the legal politics has the flavor of punishment, which is reflected in the arrangement of criminal sanctions. In its determination, referring to the error is included in the qualification of an action that can be subject to criminal sanctions or not. The purpose of this paper is to describe the regulation of criminal sanctions in large-scale social restrictions regulationsn in order to accerlerate the handling of the Covid-19 virus. The type of research used is normative research with a statutory approach, case approach, and conceptual approach. The result found that there are large-scale social restriction regulations that refer to unlawful acts which in imposing sanctions are regulated in Article 93 of Law Number 6 of 2018 concering Health Quarantine with a maximum imprisonment of 1 (one) year and a fine of Rp.100.000.000.0,- (one hundred million rupiah).